Positive and Negative Syndrome Scale and High-Density Lipoprotein Cholesterol Levels - Arneil Sitepu (GLOBAL HEALTH SCIENCE GROUP, 2024)
Schizophrenia is a chronic psychopathological disorder characterized by distortions in cognition, emotion, perception, and behavior. In addition, patients with schizophrenia have a higher risk of cardiometabolic problems, such as obesity, type 2 diabetes, hypertension, hyperglycemia, and dyslipidemia, compared to the general population. Objective to determine the correlation between the total score of the Positive and Negative Syndrome Scale (PANSS) and High-Density Lipopretein-Cholesterol (HDL-C) levels in men with chronic schizophrenia. The sampling method is non-probability sampling with consecutive sampling type with a total of 77 people. Samples that meet the inclusion criteria and are willing to participate in further research, will be interviewed with the Mini International Neuropsychiatric Interview (MINI) ICD-10 (A1) version where the diagnosis is made using diagnostic guidelines based on PPDGJ-III. If they meet the criteria, they are asked to fill out the PANSS questionnaire. This analysis uses the Pearson Correlation. The results with the correlation test between HDL-C level and total PANSS score were tested using the Pearson test. From the results above, it was obtained p-value<0.001 which indicates that there is a very significant correlation between PANSS score and HDL-C level. The Pearson correlation value of r=-0.68 suggests a negative correlation with strong correlation strength, this indicates that the lower the HDL-C level, the higher the total PANSS score. We found a negative correlation with a strong correlation, this suggests that the lower the HDL-C level, the higher the total PANSS score.